2020
DOI: 10.1037/drm0000148
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic dreaming: The effect of COVID-19 on dream imagery, a pilot study.

Abstract: COVID-19 has changed the way that people around the world live their lives, consequentially spurring various mental health difficulties. The current study aimed to determine whether people experienced distinct dream imagery during the early phase of the pandemic in Canada. The dreams of Canadian university students were recorded for 2 weeks during the beginning of Canada's experience with COVID-19. The dream imagery was analyzed and compared to a control group; t tests show that the COVID-19 group had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 27 publications
16
74
1
Order By: Relevance
“…Additionally, participants reported remembering their dreams more often during the university lockdown period. These findings are consistent with early reports of the effect of the COVID-19 lockdown on sleep: MacKay and DeCicco ( 2020 ) reported a higher incidence of location changes and animal imagery in dreams of university students during COVID-19, both of which have been linked to higher anxiety levels in previous studies (King and DeCicco, 2007 ). Schredl and Bulkeley ( 2020 ) reported greater dream recall and a higher likelihood of negative dream content during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, participants reported remembering their dreams more often during the university lockdown period. These findings are consistent with early reports of the effect of the COVID-19 lockdown on sleep: MacKay and DeCicco ( 2020 ) reported a higher incidence of location changes and animal imagery in dreams of university students during COVID-19, both of which have been linked to higher anxiety levels in previous studies (King and DeCicco, 2007 ). Schredl and Bulkeley ( 2020 ) reported greater dream recall and a higher likelihood of negative dream content during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Nightmares, with their intensified emotions, are more likely to be remembered. Thus, increased nightmares reported in our results and other studies (MacKay and DeCicco, 2020 ; Schredl and Bulkeley, 2020 ) may be indicative of a general decline in sleep quality throughout the pandemic leading to increased dream recall, rather than simply an increase in the proportion of nightmares.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A study surveying a sample of Chinese residents in Wuhan and surrounding cities showed that individuals who endorsed more post-traumatic stress symptoms (PTSS) were more likely to have poorer sleep quality (Liu et al, 2020). Studies have also found associations between the pandemic and dream quality and quantity; individuals reported more negative emotions in dreams (Schredl and Bulkeley, 2020;Gorgoni et al, 2021), increased pandemic-related dreams (MacKay and DeCicco, 2020;Pesonen et al, 2020). Among frontline medical workers, reduced sleep duration and efficiency were linked to frequent nightmares during the COVID-19 pandemic (Lin et al, 2021), highlighting the possibility of burnout and/or development of PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As to dreams with direct references to the pandemic, studies reported different frequencies of COVID-19-related dream content, varying from 8.2% (Schredl and Bulkeley, 2020) to 55% (Pesonen et al, 2020). Most dreams with pandemic-related content reflected the participants' fears of contracting the virus or close persons becoming ill or dying (Iorio et al, 2020;MacKay and DeCicco, 2020).…”
Section: Introductionmentioning
confidence: 99%